Preferensi Pengguna Twitter Terhadap Calon Presiden dan Wakil Presiden Indonesia 2024 - Adelia Tresnani; Iwan Tri Riyadi Yanto; Rahmat Hidayat (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
The 2024 Indonesian presidential election is getting closer and it’s increasingly being discussed. People’s preferences in choosing presidential and vice presidential candidates can change along with political dynamics and various activities carried out by presidential and vice presidential candidates. A politician will definitely consider their popularity if they run for president and vice president to be elected by the public. The aim of this research is to see what people’s preferences for 2024 Indonesian presidential and vice presidential candidates, especially Twitter users. In addition, this research is to measure the impact of political information spread on Twitter and provide relevant and significant insights for political decision makers, election campaign teams, and political analysts to design effective communication strategies by understanding the dynamics of people's political preferences in digital era. This research uses a combination of text mining and SAW (Simple Additive Weighting) methods to see what people’s tendencies or choices in choosing state leaders based on data from Twitter with certain hashtag and keywords that often appear on Twitter. The data collected was 92.852 tweets which were then analyzed for sentiment. Sentiment data is used in ranking process using SAW method. Sentiment results for these candidate pairs are still dominated by positive sentiment. The second candidate pair, Prabowo Subianto & Gibran Rakabuming Raka, secured the top position with a conclusive score of 0.865, trailed by the first candidate pair, Anies Baswedan & Muhaimin Iskandar, obtaining a score of 0.846. The third position was claimed by candidate pair number 3, Ganjar Pranowo & Mahfud MD, achieving a score of 0.702.